Pharmacometabolomics in TB meningitis—Understanding the pharmacokinetic, metabolic, and immune factors associated with anti-TB drug concentrations in cerebrospinal fluid - Jeffrey M. Collins; Maia Kipiani; Yutong Jin; Ashish A. Sharma; Jeffrey A. Tomalka; Teona Avaliani; Mariam Gujabidze; Tinatin Bakuradze; Shorena Sabanadze; Zaza Avaliani; Henry M. Blumberg; David Benkeser; et al. (PLoS ONE, 2025)
Poor penetration of many anti-tuberculosis (TB) antibiotics into the central nervous system (CNS) is thought to be a major driver of morbidity and mortality in TB meningitis (TBM). While the amount of a particular drug that crosses into the cerebrospinal fluid (CSF) varies from person to person, little is known about the host factors associated with interindividual differences in CSF concentrations of anti-TB drugs. In patients diagnosed with TBM from the country of Georgia (n = 17), we investigate the association between CSF concentrations of anti-TB antibiotics and multiple host factors including serum drug concentrations and CSF concentrations of metabolites and cytokines. We found > 2-fold differences in CSF concentrations of anti-TB antibiotics from person to person for all drugs tested including cycloserine, ethambutol, imipenem, isoniazid, levofloxacin, linezolid, moxifloxacin, pyrazinamide, and rifampin. While serum drug concentrations explained over 30% of the variation in CSF drug concentrations for cycloserine, isoniazid, linezolid, and pyrazinamide (adjusted R 2 ≥ 0.3, p < 0.001 for all), there was no significant association between serum concentrations of imipenem and ethambutol and their respective CSF concentrations. CSF concentrations of carnitines were significantly associated with concentrations of ethambutol and imipenem (q < 0.05), and imipenem was the only antibiotic significantly associated with CSF cytokine concentrations. These results indicate that there is high interindividual variability in CSF drug concentrations in patients treated for TBM, which is only partially explained by differences in serum drug concentrations. With the exception of imipenem, there was no association between CSF drug concentrations and concentrations of cytokines and chemokines.